Accountability of Building Permit Services in Buton Regency - Rahmawati Rahmawati; La didi; Asrul Asrul (Sean Institute, 2025)
This study aims to explore the accountability of building approval services at the Investment and One-Stop Integrated Service Office (DPMPTSP) of Buton Regency; procedures in building approval services, cost certainty, time standards and responsiveness. Data collection techniques are carried out through interview methods, observation, documentation, and online data search methods, data analysis techniques are carried out through data reduction, and drawing conclusions. The findings of this study indicate that the Accountability of Building Construction Permit Services in Buton Regency, as a whole, is not fully accountable, there are still several dimensions that are considered inadequate as follows: “1. The service procedure is not in accordance with the SOP contained in the standard service standards, the public still does not know much about the change in regulations from IMB to PBG, socialization has not been carried out so that the public is confused about taking care of building permits, 2. Transparent financing according to community expectations, financing is regulated in regional regulation number 6 of 2023 concerning Regional Taxes and Regional Retributions although there are still several points that are different from the previous IMB retribution, such as technical standard compliance inspection services, PBG issuance, and building inspections but are still carried out manually. 3. The time period for processing PBG regulations at the Buton Regency PUPR DPUPR is not in accordance with the applicable provisions and SOPs. During the transition period, the IMB regulation is still the patron in serving PBG permits which has an impact on the process of adapting online-based PBG licensing services, in terms of the division of the implementation of PBG licensing services involving two (2) agencies which has implications for the service process which takes a long time and is not on time”. 4. The responsiveness of the PUPR Service of Buton Regency is quite good, the PUPR service and related officers quickly respond to complaints and complaints from the public so that the public can understand the mechanism of PBG licensing regulations.